2022
DOI: 10.3389/fneur.2021.800605
|View full text |Cite
|
Sign up to set email alerts
|

Migraine: A Review on Its History, Global Epidemiology, Risk Factors, and Comorbidities

Abstract: Migraine affects more than one billion individuals each year across the world, and is one of the most common neurologic disorders, with a high prevalence and morbidity, especially among young adults and females. Migraine is associated with a wide range of comorbidities, which range from stress and sleep disturbances to suicide. The complex and largely unclear mechanisms of migraine development have resulted in the proposal of various social and biological risk factors, such as hormonal imbalances, genetic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 183 publications
(380 reference statements)
5
104
0
11
Order By: Relevance
“…Investigators have identified some brain alterations in DMN regions in migraine ( Liu et al, 2015 ), fibromyalgia ( Pujol et al, 2014 ), and knee osteoarthritis ( Pujol et al, 2017 ). The decreased CBF values of the precuneus exhibited in our study may suggest the impairment of DMN which is common in chronic pain-related diseases and is consistent with the previous study ( Amiri et al, 2021 ). The superior occipital gyrus is continuous along the superomedial margin of the hemisphere with the cuneus and is involved in many complex functions of the human body.…”
Section: Discussionsupporting
confidence: 93%
“…Investigators have identified some brain alterations in DMN regions in migraine ( Liu et al, 2015 ), fibromyalgia ( Pujol et al, 2014 ), and knee osteoarthritis ( Pujol et al, 2017 ). The decreased CBF values of the precuneus exhibited in our study may suggest the impairment of DMN which is common in chronic pain-related diseases and is consistent with the previous study ( Amiri et al, 2021 ). The superior occipital gyrus is continuous along the superomedial margin of the hemisphere with the cuneus and is involved in many complex functions of the human body.…”
Section: Discussionsupporting
confidence: 93%
“…Migraine is a complex brain disease affecting more than 1 billion people worldwide and is the main cause of disability in the world population. In the past three decades, the global incidence rate of migraine has increased significantly, resulting in serious disease and economic burdens (Amiri et al, 2021;Ashina et al, 2021;Safiri et al, 2022). The International Headache Association defines migraine as a recurrent primary headache disorder that lasts for 4-72 h. Generally, headache is single, pulsatile, moderate or severe, aggravated by routine physical activity, and accompanied by nausea, photophobia, and hydrophobia (Headache Classification Committee of the International Headache Society [IHS], 2013).…”
Section: Introductionmentioning
confidence: 99%
“…К психологическим особенностям личности пациентов с мигренью относят перфекционизм, завышенные требования к себе и к окружающим, нейротизм (эмоциональную неустойчивость), ипохондричность, высокую личностную тревожность, склонность к чрезмерным эмоциональным реакциям. Авторы предшествующих исследований обнаружили, что перечисленные психологические характеристики значимо чаще встречаются среди пациентов с мигренью, чем в общей популяции [19]. Также было показано, что люди с мигренью сильнее реагируют на стресс, тяжелее переживают негативные жизненные события, чем люди без мигрени [20].…”
Section: Relationship Between Individual Psychological Characteristic...unclassified
“…Активная жизненная позиция рассматривается как одна из психологических особенностей личностей с мигренью. Есть публикации, в которых обсуждается взаимосвязь мигрени, талантливости и известности, так как многие известные деятели в области политики, науки и культуры страдали мигренями [19].…”
Section: Relationship Between Individual Psychological Characteristic...unclassified